Benchmarking in primary health care: An application of the stochasticd frontier analysis and the grades of membership approach to Portuguese family health units - Neves, Ana Catarina Arranhado (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Economics from the NOVA – School of Business and Economics